Elimination of Discrimination Against Women in Labor Relations and Labor Rights Guarantees (Texas Journal of Multidisciplinary Studies, 2023)
This article analyzes women's rights, elimination of all forms of discrimination of women's rights, improvement of labor legislation regulating women's rights in the field of work, mechanisms to fight against violation of women's rights